Bibliography of Acad. Hans Em - Papazova-Anakieva, Irena; Nacheski, Sterja; Koljozov, Vladimir; Simovski, Bojan (Ss. Cyril and Methodius university in Skopje, Faculty of Forestry in Skopje, 2013)
Acad. Hans Em is one of the founders of modern forestry in Macedonia and the Faculty of Forestry in Skopje. He was the only forest-sector member of the Macedonian Academy of Sciences and Arts, a distinguished professor and dean of the Faculty of Forestry in Skopje. Acad. Em has discovered many new woody species for the forestry science, new founding sites of plants and new forest communities for the time he researched. He was author and co-author of more than a hundred very important papers and vegetation maps concerning the Macedonian and Balkan dendroflora and forest vegetation. This 2013 is a jubilee year -115 years of his birth. Therefore, in this monograph article are previewed all paper works of Acad. Hans Em i.e. his bibliography and most important scientific achievements.
Monograph article
Keywords: bibliography; monograph; Hans Em